(untitled) (The Pakistan Development Review, 2000)
Trade plays a vital role in determining the growth process of any country. Trade liberalisation and openness of the economy are now almost universally accepted as the main ingredients of successful economic growth and welfare of the population. These are believed to be responsible for the exceptional growth of industrialised and newly industrialised countries. Many developing countries, under the auspices of the WTO are taking major steps to liberalise their trade regimes. However, in the short run, the impact of these policy changes is generally perceived to be painful for both the producers and the consumers; and especially so for the latter. A key question here is the impact of trade reforms on poverty, which has persisted in most developing countries despite concerted efforts on many fronts to eradicate this social evil. Like many developing countries, Pakistan has undertaken far-reaching trade reforms aimed at creating an open international trading environment. Pakistan’s dependence on international trade, as measured by the total trade to GDP ratio, has increased significantly from 13.3 percent in 1960-61, to 32.47 percent in 1992-93. As such, it is important to determine if there is a relationship between trade liberalisation and poverty alleviation; do trade reforms lead to reduction in country wide poverty levels or not.